Luminescence Microscopy in the Identification of Closely related Species Using the Example of the Genus Persicaria Mill. - A. A. Gudkova; A. S. Chistyakova; A. I. Slivkin; A. S. Bolgov (Разработка и регистрация лекарственных средств, 2024)
Introduction. The issue of standardization and quality assessment of medicinal plant materials is currently one of the most important. To do this, a number of parameters are evaluated, the primary of which is the assessment of the authenticity of the analyzed plant object. The problem of identifying official species in the presence of closely related species is typical for plants belonging to the genus Persicaria Mill., among which only two species are used in medical practice and there is regulatory documentation for the herbs of these plants. The similarity of morphological and anatomical features of plant species acceptable for medical use and impurities interprets the need to use additional modern methods of analysis. One of such selective methods for diagnosing plant materials, along with the well-known and used in pharmaceutical analysis, is luminescence microscopy.Aim. The goal was to study the features of the luminescence of closely related species of the genus Persicaria Mill. to improve the process of their identification and standardization of official types of raw materials.Materials and methods. For work, 10 species of the genus Persicaria Mill. were used from families Polygonaceae Juss., most common in the Central Chernozem region: P. maculosa Gray, P. tomentósa Bicknell, P. lapathifólia Delarbre, P. nodósa Opiz, P. scábra Moldenke, P. brittingeri Opiz, P. hydropiper Delarbre, P. minor Opiz, P. amphibia Delarbre, P. amphibia var. terrestris Munshi & Javeid. The plants were cut at a height of about 15 cm from the soil during mass flowering in the summer of 2020 in the Voronezh region, dried in the shade. Previously, before the study, the plants were divided into morphological components (stems, leaves, petioles, bells, flowers, fruits), for which herbarium samples were used in dried form and individual parts were examined, straightened on a glass slide. To assess the luminescence of objects, a Micromed-3 Lum microscope (Russia) with a luminescent nozzle housing was used.Results and discussion. It was revealed that the intense fluorescence of large trichomes, the conducting system, guard cells of stomata, thickening of cell walls, and, in some species, the contents of receptacles and glands, is common to all studied species. A number of characteristic features of tissue luminescence for the studied species have been revealed: P. hydropiper has numerous brightly luminous receptacles and glands on all morphological parts. For P. maculosa, the presence of large receptacles along the veins was established for the first time. The perianth, glandules, and filiform hairs of the bell of P. brittingeri are clearly visible and have a yellowish-green luminescence. The leaf glands of P. tomentósa, unlike other species, do not have luminescence. The perianths of P. scábra and P. tomentósa have a yellowish-orange glow. The membranous trichomes are clearly visible in P. lapathifólia and stand out with a brownish tint. The largest number of long tufted trichomes with a bright greenish glow is characteristic of P. amphibia var. terrestris.Conclusion. The method of luminescence microscopy was first applied to the analysis and identification of identification parameters, new diagnostic features were established and visualized, allowing the most accurate identification of species of the genus Persicaria.